Application Evaluation of High-Flow Humidified Oxygen in Patients with Respiratory Failure after General Anesthesia Extubation for Multiple Injuries. (16th August 2021) - Ci, Ruijuan; Qin, Yanjun; Ci, Caizhe; Zhang, Chunhua; Dong, Shimin; Li, Mei
Abstract : Objective . To explore the effect of high-flow humidified oxygen therapy (HFNC) on patients with respiratory failure after general anesthesia extubation for multiple injuries. Methods . 214 patients with multiple injuries in our hospital who underwent general anesthesia and suffered respiratory failure after weaning extubation and received sequential treatment were included. And, they were divided into control group (HFNC group) and observation group (NIMV group) according to the random number table method. Patients in the control group (125 cases) used high-flow nasal cannula (HFNC) after general anesthesia extubation, while patients in the observation group (89 cases) used NIMV. The respiratory rate, heart rate, finger pulse oxygen, oxygenation index (PaO2 /FiO2 ), and re-tracheal intubation rate in the two groups were compared at 2, 8, and 24 hours after sequential treatment, and the mortality rate and hospital stay of ICU time were whole-course observation. And, the effect of conventional oxygen inhalation or HFNC on oxygenation and prognosis was analyzed. Then, SPSS21.0 software was applied for statistical analysis. To analyze the effect of conventional oxygen inhalation or HFNC on the improvement of oxygenation and prognosis, the receiver operating characteristic (ROC) curve can be used to evaluate the feasibility and treatment effect of high-flow nasal oxygen therapy (HFNC) for patients with respiratory failure after general anesthesia extubation for multiple injuries. Results . Compared with the NIMV group, the respiratory frequency and heart rate of the HFNC group were significantly improved after 2 h, 8 h, and 24 h. At the same time, the finger pulse oxygen and oxygenation index increased significantly and returned to normal levels. HFNC can significantly reduce the reintubation rate, ICU hospital stay, and mortality rate. The area under the ROC curve was 0.9102, with 95% CI (0.8256, 0.9949) and P < 0.0001 . Conclusion . For patients with multiple injuries undergoing general anesthesia and respiratory failure after weaning and extubation, the application of HFNC can moderate patients' heart rate and respiratory rate faster, increase oxygenation index and finger pulse oxygen, and reduce the reintubation rate, mortality rate, and ICU stay. At the same time, it can effectively improve the respiratory failure of patients after extubation and reduce the occurrence of complications.